BASS XXXI: Outflow scaling relations in low redshift X-ray AGN host galaxies with MUSE. Issue 2 (17th January 2022) - Kakkad, D; Sani, E; Rojas, A F; Mallmann, Nicolas D; Veilleux, S; Bauer, Franz E; Ricci, F; Mushotzky, R; Koss, M; Ricci, C; Treister, E; Privon, George C; et al.
ABSTRACT: Ionized gas kinematics provide crucial evidence of the impact that active galactic nuclei (AGNs) have in regulating star formation in their host galaxies. Although the presence of outflows in AGN host galaxies has been firmly established, the calculation of outflow properties such as mass outflow rates and kinetic energy remains challenging. We present the [O iii ]λ5007 ionized gas outflow properties of 22 z<0.1 X-ray AGN, derived from the BAT AGN Spectroscopic Survey using MUSE/VLT. With an average spatial resolution of 1 arcsec (0.1–1.2 kpc), the observations resolve the ionized gas clouds down to sub-kiloparsec scales. Resolved maps show that the [O iii ] velocity dispersion is, on average, higher in regions ionized by the AGN, compared to star formation. We calculate the instantaneous outflow rates in individual MUSE spaxels by constructing resolved mass outflow rate maps, incorporating variable outflow density and velocity. We compare the instantaneous values with time-averaged outflow rates by placing mock fibres and slits on the MUSE field-of-view, a method often used in the literature. The instantaneous outflow rates (0.2–275 M ⊙ yr −1 ) tend to be two orders of magnitude higher than the time-averaged outflow rates (0.001–40 M ⊙ yr −1 ). The outflow rates correlate with the AGN bolometric luminosity ( L bol ∼ 10 42.71 –10 45.62 erg s −1 ) but we find no correlations with black hole mass (10 6.1 –10 8.9 M⊙ ), Eddington ratio (0.002–1.1), and radio luminosity (10 21 –10 26 W Hz −1 ). We find the median coupling between the kinetic energy and L bol to be 1 per cent, consistent with the theoretical predictions for an AGN-driven outflow.